Variant pubertal development in Prader-Willi syndrome: early and slow progression of pubarche with normal age at gonadarche - Kodytková, Aneta; Dušátková, Petra; Amaratunga, Shenali Anne; Koloušková, Stanislava; Obermannová, Barbora; Pomahačová, Renata; Průhová, Štěpánka; Šnajderová, Marta; Šumník, Zdeněk; Zapletalová, Jiřina; Semjonov, Valerij; Lebl, Jan (Frontiers in Endocrinology, 2025)
IntroductionPrader-Willi syndrome (PWS) is primarily caused by a paternal microdeletion of the 15q11-q13 region, maternal uniparental disomy (mUPD) or unbalanced translocations. The MKRN3 gene, located within 15q11-q13, is a master regulator of pubertal initiation. We aimed to compare variant pubertal onset and progression with recent normative data and to correlate it with abnormal MKRN3 gene status.MethodsAge at pubarche, gonadarche, subsequent pubertal progression and bone age (BA) at gonadarche were investigated in 37 PWS patients (18 females) who already entered pubarche and/or gonadarche with median age 11.1 (95% CI: 6.4 – 18.8) years. All patients were re-tested to confirm genetic subtypes of PWS. The MKRN3 gene was analyzed using single gene sequencing.ResultsOut of 37 subjects, 22 had microdeletion and 15 mUPD. Regardless of genetic subtypes and MKRN3 gene status, no correlation between genotypes and the pubertal pattern was found. They initiated pubarche early – girls at 7.4 (95%CI:6.4–8.4), and boys at 9.2 (8.2–10.2) years. The subsequent progression from PH2 to PH4 (pubic hair development) was prolonged to 3.7 years in girls (1.5–5.9;p<0.05), and 2.9 in boys (2.2–3.6;p<0.001). The age at gonadarche was adequate – 10.0 years in girls (8.8–11.2), and 11.0 in boys (9.8–12.1). Progression rate of breast development from B2 to B4 was 3.9 (0.2–7.5) years in girls and of testicular volume from 4 ml to 15ml was 3.8 (0.0–8.1) years in boys. The BA at gonadarche is advanced by 0.6 ± 1.1 years (p<0.001).ConclusionsChildren with PWS, regardless of the genetic subtype and/or MKRN3 status, had an early pubarche and normally timed gonadarche. Pubarche progression was slower. Advanced BA was significantly correlated with gonadarche.